#### Answer

(a) $f(x) = \frac{2}{5}x+\frac{9}{5}$
(b) $f(3) = 3$

#### Work Step by Step

(a) function notation.
Solve for $y$:
\begin{array}{ccc}
&-2x+5y&=&9
\\&-2x+5y+2x&= &9+2x
\\&5y&=&2x+9
\\&\frac{5y}{5}&=&\frac{2x+9}{5}
\\&y&=&\frac{2}{5}x+\frac{9}{5}
\end{array}
Let $y=f(x)$. The equation becomes:
$$f(x)=\frac{2}{5}x+\frac{9}{5}$$
(b) To find $f(3)$, substitute $3$ to $x$ in $f(x)$ to obtain:
$f(x)= \frac{2}{5}x+\frac{9}{5}
\\f(3) = \frac{2}{5}(3)+\frac{9}{5}
\\f(3)=\frac{6}{5}+\frac{9}{5}
\\f(3)=\frac{15}{5}
\\f(3)=3$